Professional competencies and graduates employability in Oman - Al Harrasi, Ghanim Faiz; Al Salmani, Masoud Suliman; Al Harrasi, Maram Ghanim (Institute of Advanced Engineering and Science, 2025)
The unemployment crisis among graduates is a global issue that receives considerable attention from countries. However, in the Omani context, employers and policymakers argue that it stems from a lack of professional competencies rather than a shortage of jobs. Therefore, this paper focuses on studying the impact of graduates’ professional competencies on employability from the perspective of graduates of the University of Technology and Applied Sciences (UTAS) in Oman. The study examines graduates’ perceptions of professional competencies that directly affect employability within the context of the Omani labor market. It explores the relationship between Omani graduates’ professional competence and the skills gap between graduates and the requirements of the labor market in Oman. The study employed a quantitative approach, with data collected via a questionnaire distributed to 100 graduates from the UTAS in Oman. The study applied exploratory factor analysis using SPSS to test the factors influencing graduates’ employability. The main findings concluded that graduates believe they are professionally competent but cannot identify a consensus on the competence barrier preventing them from being employed. Based on these findings, the study recommends a unified guideline of competencies required by Oman’s labor market.